Treatment of Young Permanent Avulsed Teeth with Multidisciplinary Approach—A Case Report - Narda Lorena Rivera-Pimentel; Nadia Phenelope Campos-Lara; Oscar Arturo Benítez-Cárdenas; Verónica Méndez-González; Andreu Comas-García; Marlen Vitales-Noyola; Gabriela Torre-Delgadillo (Dentistry Journal)
Background: Dental trauma very commonly comprises lesions that affect the teeth and their supporting structures. In pediatric ages, the main reasons for dental trauma are falls and accidents at school and while practicing recreative activities and sports. Fortunately, dental avulsions are not common; however, they are key factors in the loss of teeth if the issue is not adequately treated in a quick way, so is very important for parents, teachers, or any person that is present with a child during the accident to have knowledge about dental trauma, specifically regarding avulsed teeth, since the best treatment is reimplantation. Methods: In this case of dentoalveolar trauma, concerning two avulsed teeth, it was very interesting that the tooth that was reimplanted more quickly (40 min) had a worse prognosis than the tooth that was reimplanted 2 h later, since the tooth that was reimplanted more quickly was transported in a personal wallet, which was a highly contaminated area, unlike the tooth that was reimplanted later, which was transported in a solution as an alternative means of transport. Conclusions: So, it is very important that this type of trauma is adequately managed in an interdisciplinary way across multiple dentistry specialties.